Computational Optimization of Model BRASIL-SR - de Souza, Jefferson Gonçalves; Mendes, Celso Luiz; Costa, Rodrigo Santos (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2018: Anais do XIX Simpósio em Sistemas Computacionais de Alto Desempenho, 2018)
This paper describes the improvement of computational performance of the BRASIL-SR model. This computational code, which is used for the estimate of incident surface solar radiation, was optimized with an application of OpenMP directives and code modifications for the implementation of data output (I/O) operations using NetCDF format files. After these implementations, it was verified that the speedup of the code was further improved with the I/O optimizations, with a more stable efficiency, which shows a better use of the processors in the underlying supercomputer.